The SAGE international encyclopedia of travel and tourism - Lowry, Linda L. (Thousand Oaks, California : SAGE Publications, Inc., 2017)
Taking a global and multidisciplinary approach, The SAGE International Encyclopedia of Travel and Tourism brings together a team of international scholars to examine the travel and tourism industry, which is expected to grow at an annual rate of four percent for the next decade. In more than 500 entries spanning four comprehensive volumes, the Encyclopedia examines the business of tourism around the world paying particular attention to the social, economic, environmental, and policy issues at play. The book examines global, regional, national, and local issues including transportation, infrastructure, the environment, and business promotion.
Includes bibliographical references and index.
Description based on MARC record for print version.
Keywords: Tourism -- Encyclopedias